Gallstones and Choledocolithiasis with Severe Cholestatic Jaundice in beta-Thalasemia Intermedia Patient - Suharjo B Cahyono; Putut Bayupurnama; Neneng Ratnasari; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Geographically, b-thalassemia can be found in many countries including in Indonesia. Thalassemia intermedia referred to patients as being ‘too haematologically severe to be called minor, but too mild to be called major’. Patients with thalassemia intermedia usually present themselves to medical attention in later childhood or even adulthood and are sustainable without the need for regular transfusion therapy. Three main factors are responsible for the clinical sequele of thalassemia intermedia: chronic anemia, ineffective erythropoiesis, and iron overload.There are many complications related to b-thalassemia intermedia such as gastroentero-hepatology diseases (splenomegaly, gallstones, choledocolithiasis, predispose patients to liver fibrosis and cirrhosis), vascular, endocrine and bone diseases. About 55-63% thalassemia intermedia patients suffer from gallstone with 68–85% of these patients undergo cholecystectomy, and 67-90% patients undergo splenectomy. Therefore, ultrasound examination is required to be performed regularly during illness and before patient underwent surgery or splenectomy to detect the presence of gall stones. In this case report a patient with gallstones and choledocholithiasis was reported. Severe cholestatic jaundice in b-thalassemia intermedia was diagnosed six months before hospitalization. The patient underwent open cholecystectomy and exploration common bile duct stones. Keywords: beta-thalassemia intermedia, gallstones, choledocolithiasis, iron overload